Contextual Factors and Motor Skills in Indigenous Amazon Forest and Urban Indigenous Children - Duarte, Marcelo Gonçalves; Valentini, Nadia Cristina; Nobre, Glauber Carvalho; Benda, Rodolfo Novellino (Frontiers in Public Health, 2022)
This study investigated the contextual factors, motor performance, and body mass index across indigenous land children, indigenous urban children, and non-indigenous urban children. A number of 153 children, both sexes (71 girls, 46.4%), from 8 to 10 years were assessed. The Test of Motor Gross Development-3 was utilized. Indigenous land children showed higher motor performance (η2ρ = 0.37 and η2ρ = 0.19 locomotor and object control, respectively) than indigenous urban children (p < 0.03) and non-indigenous urban children (p < 0.01); Indigenous urban children showed higher motor performance than non-indigenous urban children (p < 0.01). Body mass index was similar across groups (η2ρ = 0,02; p = 0.15). Motor performance of indigenous land children was explained by the contextual factors that lead to a more active lifestyle, unsupervised free time, and play outside. In urban areas, behavior was similar, and although indigenous urban children kept some play tradition, it was not strong enough to be a protective factor for the motor performance.